Lavender and Clotrimazol Effect on the Growth Standard Strains of C. Albicans in Vitro Conditions - F Behmanesh (Babol University of Medical Sciences, 2010)
BACKGROUND AND OBJECTIVE: Gynecologic infections are the most common causes that women see a doctor. With regard to the high prevalence of vaginal candidiasis infections and side effects of chemical drugs and also reduction of their effectiveness against resistant strains, this study was designed to compare the effects of lavender and clotrimazole on the growth standard strains of Candida albicans in vitro conditions. METHODS: In this semi-experimental study, laboratory method of fungi cell counts by toma hemasimeter slide was used. In this method, after preparing dilution of 6 × 106 from standard Candida albicans S.C.a-PTCC-2657 in the liquid Saburo culture media and also add lavender essential oil, steam and clotrimazole in different dilution of (½, ¼, 1/8) and putting them into incubator for 48 hours (in 4 laboratory stages), fungal cell count was done with attention to inhibition of standard Candida multiplication. The tests were repeated twice for every drugs in different dilution of (½, ¼, 1/8). Samples characteristics and tests results were collected and compared.FINDINGS: The findings of this study showed that the number of fungi in test tubes which contained the lavender essential oil, lavender steam in comparison to control fungi had decreased dramatically (17× 106, 0.4×106 vs 188×106, respectively). Also, the count of fungal cell in the dilution ½ of drugs, the lavender steam was less than lavender essential oil and clotrimazole and in dilution of ¼ and 1/8, the lavender essential oil in comparison to lavender steam and clotrimazol had less count of fungi. The most antifungal efficacy of drugs was in the higher diluted. As among different dilutions (½, ¼ and 1/8), the lavender essential oil in dilution of ¼ and 1/8, and the lavender steam in dilution of 1/8 had been the more antifungal effect. In the all above dilutions, clotrimazole had the lowest antifungal efficacy and the most fungi cell counts.CONCLUSION: The results showed that the lavender essential oil and steam had more antifungal effect and efficacy against the standard Candida albicans in comparison to clotrimazole.